The Fungal Pathogen Candida albicans Autoinduces Hyphal Morphogenesis by Raising Extracellular pH - Slavena Vylkova (American Society for Microbiology, 2011)
ABSTRACT pH homeostasis is critical for all organisms; in the fungal pathogen Candida albicans, pH adaptation is critical for virulence in distinct host niches. We demonstrate that beyond adaptation, C. albicans actively neutralizes the environment from either acidic or alkaline pHs. Under acidic conditions, this species can raise the pH from 4 to >7 in less than 12 h, resulting in autoinduction of the yeast-hyphal transition, a critical virulence trait. Extracellular alkalinization has been reported to occur in several fungal species, but under the specific conditions that we describe, the phenomenon is more rapid than previously observed. Alkalinization is linked to carbon deprivation, as it occurs in glucose-poor media and requires exogenous amino acids. These conditions are similar to those predicted to exist inside phagocytic cells, and we find a strong correlation between the use of amino acids as a cellular carbon source and the degree of alkalinization. Genetic and genomic approaches indicate an emphasis on amino acid uptake and catabolism in alkalinizing cells. Mutations in four genes, STP2, a transcription factor regulating amino acid permeases, ACH1 (acetyl-coenzyme A [acetyl-CoA] hydrolase), DUR1,2 (urea amidolyase), and ATO5, a putative ammonia transporter, abolish or delay neutralization. The pH changes are the result of the extrusion of ammonia, as observed in other fungi. We propose that nutrient-deprived C. albicans cells catabolize amino acids as a carbon source, excreting the amino nitrogen as ammonia to raise environmental pH and stimulate morphogenesis, thus directly contributing to pathogenesis. IMPORTANCE Candida albicans is the most important fungal pathogen of humans, causing disease at multiple body sites. The ability to switch between multiple morphologies, including a rounded yeast cell and an elongated hyphal cell, is a key virulence trait in this species, as this reversible switch is thought to promote dissemination and tissue invasion in the host. We report here that C. albicans can actively alter the pH of its environment and induce its switch to the hyphal form. The change in pH is caused by the release of ammonia from the cells produced during the breakdown of amino acids. This phenomenon is unprecedented in a human pathogen and may substantially impact host physiology by linking morphogenesis, pH adaptation, carbon metabolism, and interactions with host cells, all of which are critical for the ability of C. albicans to cause disease.